Failure analysis of BMC insulators used for third rail traction system. (July 2019) - Subba Reddy, B.
Abstract: Bulk molding compound (BMC) or Glass Reinforced plastic (GRP) composite insulators are extensively used for the third rail electric traction system. The performance of these insulators primarily depends on the local environmental conditions that cause degradation over a period of time. Degradation leads to partial arcing which grow more severe and can generate combustion that ignites flammable debris, smoke including fires resulting in service interruptions and safety risks of the third rail traction system. In the present investigations, exhaustive analysis is conducted to understand the root cause of degradation and arcing on the field aged insulators rated for 750Vdc. Leakage current and surface resistance measurements are conducted under dry, wet and contaminated conditions. Further to better interpret Physico-chemical analysis are conducted using Scanning Electron Microscopy (SEM), Energy Dispersive X-Ray (EDAX) and Fourier Transform Infra-Red (FTIR) spectroscopy to investigate surface morphology and chemical changes in the samples, also Thermo-Gravimetric Analysis (TGA) is performed to find the thermal characteristics of the insulator. Interesting results obtained from the investigations clearly present evidence to loss of epoxy material from the bulk eventually leading to the exposure of glass fibers causing degradation, arcing and failure of the insulators. The study further highlights the essential procedures to be edopted to locate, isolate, and better anticipate failures of BMC insulators used in third rail traction system. Highlights: Failure analysis conducted on BMC insulators used for third rail traction system. Leakage current and surface resistance measurements are analyzed. Results of surface morphological changes using SEM, FTIR, TGA reported. Investigations on material degradation and remedial measures presented.